The Relationship Between Health Locus of Control and Vulnerability and Treatment Adherence in Pulmonary TB Patients at Setio Husodo Hospital: Health Locus of Control and Vulnerability - Zulfahri Lubis; Indahwati; Kristina; Afrizal Hasan (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
ABSTRACT The rise in the count of tuberculosis patientss tems from the low degreeof patient adherence in using anti-tuberculosis medications,which is impacted by the level of insight regarding tuberculosis,drive to heal,remoteness,health care expenses, drug adverse effects,familial backing, and the function of medical personnel.. This study is to determine the relationship between Health Locus of Control and Vulnerability with Treatment Compliance in Tuberculosis patients. The sort of research carried outis an analytical design poll utilizin ga cross- sectional perspective, the quantity of samples in this investigation comprised 27 pulmonary TB sufferers via purposive selection. The data analysis used was Rank Spearman. The findings of the research indicated a noteworthy association between Health Locus of Control and Treatment Adherence among Pulmonary TB sufferers. 0.000 < 0.05,featuring a correlation coefficient of 0.877. There is a significant relationship between vulnerability and Treatment Compliance in Pulmonary TB patients. 0.001 < 0.05. with a correlation coefficient of 0.598. The conclusion of this study is that there is a relationship between Health locus of control and Vulnerability with Treatment Compliance in Pulmonary TB Patients. It's hoped that with this research, health care staff will be more proactive in delivering health in struction concerning dimensions of locus of control, susceptibility to adhering to pulmonary TB therapy.